Secondary Institutional Betrayal: Implications for Observing Mistreatment of Sexual Assault Survivors Secondhand - PettyJohn, Morgan E. (Journal of interpersonal violence, 2023)
Institutional betrayal has been used to describe the experiences of sexual assault survivors who are harmed by institutions which they rely on for safety or survival. This concept has primarily been studied in the context of survivors’ direct relationships with institutions they are members of (e.g., universities, churches, military) and how the said institutions either failed to protect them or were unsupportive following their disclosure. Institutional betrayal can exacerbate negative mental and physical health outcomes for survivors, highlighting a need to hold institutions accountable for harm they cause. A limitation to this conceptualization is that many adults in the general public are not proximally connected to institutions (as they have historically been defined), and the majority of survivors do not formally report. Drawing on semi-structured interviews conducted with young women survivors (n = 12), the present study aims to address this gap by abstracting the conceptualization to a more macro level, proposing the term secondary institutional betrayal. Secondary institutional betrayal refers to survivors’ feelings of mistrust and disillusionment toward institutions they are distally connected to which are not directly involved in their own assault (e.g., the media, U.S. government, U.S. criminal legal system, their university), yet still have influence over their personal safety and survival. This sense of betrayal stems from secondhand observations, through the news media, of how other survivors are treated by these institutions. Many survivors in the present study reported their secondhand observations of institutional betrayal would likely deter them from reporting future assaults. Establishing research in this area is important to understand how survivors in the general public are impacted by news stories which highlight institutional betrayal, particularly in the context of ongoing social movements (e.g., #MeToo) which amplify public discourse about sexual assault.